Lucid nightmares: an exploratory online study - Schredl, Michael; Bulkeley, Kelly (International journal of dream research, 2020)
Lucid nightmares are defined as dreams with strong negative emotions in which the dreamer is aware that he or she is dreaming but is unable to change the terrifying plot of the dream and/or is unable to deliberately wake up from it. So far, very little is known about lucid nightmare content. A subsample of a representative survey consisting of 408 participants (248 women, 160 men) with a mean age of 43.54 ± 16.04 yrs. provided a most recent lucid dream experience. Of the 160 nightmarish dreams, 67 could be classified as lucid nightmares with two thirds of the dreams including the inability to wake up. “Including nightmarish elements in the most recent lucid dream report” and “Being able to change the distressing content vs. having a lucid nightmare” was not related to age, gender, education, and ethnicity in this exploratory study. Future studies should focus on the variety of lucid nightmare topics - possibly expand the definition as this is currently focused on the inability to wake up or not being able to change the plot - and intervention strategies, i.e., the most effective ways to deal with lucid nightmares.
Gesehen am 19.10.2020